Assessment of in vitro kinetics and biological impact of nebulized trehalose on human bronchial epithelium. (November 2021) - Iskandar, Anita R.; Kolli, Aditya Reddy; Giralt, Albert; Neau, Laurent; Fatarova, Maria; Kondylis, Athanasios; Torres, Laura Ortega; Majeed, Shoaib; Merg, Celine; Corciulo, Maica; Trivedi, Keyur; Guedj, Emmanuel; et al.
Abstract: Trehalose is added in drug formulations to act as fillers or improve aerosolization performance. Its characteristics as a carrier molecule have been explored; however, the fate of trehalose in human airway tissues has not been thoroughly investigated. Here, we investigated the fate of nebulized trehalose using in vitro human air-liquid bronchial epithelial cultures. First, a tracing experiment was conducted using 13 C12 -trehalose; we measured trehalose distribution in different culture compartments (apical surface liquid, epithelial culture, and basal side medium) at various time points following acute exposure to 13 C12 -labeled trehalose. We found that 13 C12 -trehalose was metabolized into 13 C6 -glucose. The data was then used to model the kinetics of trehalose disappearance from the apical surface of bronchial cultures. Secondly, we evaluated the potential adverse effects of nebulized trehalose on the bronchial cultures after they were acutely exposed to nebulized trehalose up to a level just below its solubility limit (50 g/100 g water). We assessed the ciliary beating frequency and histological characteristics. We found that nebulized trehalose did not lead to marked alteration in ciliary beating frequency and morphology of the epithelial cultures. The in vitro testing approach used here may enable the early selection of excipients for future development of inhalation products. Graphical abstract: Image 1